The festival of moors and christians as pillar of the arts. - Martínez Pozo, Miguel Ángel; Anta Félez, José-Luis (Calle 14 revista de investigación en el campo del arte, 2016)
ABSTRACT The Festivals of Moors and Christians represents a unique and concrete world that crosses both the history and geography of Spain and its social, political and economic configurations. Historically, they have had a pedagogical sense and, for that reason, they present the complexity of different events, elements, objects and actors that compose it as contrasting elements (assimilation of nationalism and regionalisms or the eternal Hispanic struggle between good and evil), making everything appear normal, exerting a power that few celebrations hold. These chameleonic feasts have adapted to different historical moments and, with the coming of postmodernity, have opened their gates to a colorful game of fantasy where visual and performing arts have become of the utmost importance.